2015
DOI: 10.1038/ncomms8710
|View full text |Cite
|
Sign up to set email alerts
|

Plant species’ origin predicts dominance and response to nutrient enrichment and herbivores in global grasslands

Abstract: Exotic species dominate many communities; however the functional significance of species' biogeographic origin remains highly contentious. This debate is fuelled in part by the lack of globally replicated, systematic data assessing the relationship between species provenance, function and response to perturbations. We examined the abundance of native and exotic plant species at 64 grasslands in 13 countries, and at a subset of the sites we experimentally tested native and exotic species responses to two fundam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

14
179
7

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 158 publications
(200 citation statements)
references
References 48 publications
14
179
7
Order By: Relevance
“…In particular, fewer native species were lost in response to nutrient addition in warmer, wetter sites. This is contrary to previous findings that suggest that nutrient enrichment reduces native species richness and increases non-native species richness independently of climate [10,39]. Rare species tend to be lost from communities with nutrient enrichment (particularly N) [8].…”
Section: Discussioncontrasting
confidence: 91%
See 3 more Smart Citations
“…In particular, fewer native species were lost in response to nutrient addition in warmer, wetter sites. This is contrary to previous findings that suggest that nutrient enrichment reduces native species richness and increases non-native species richness independently of climate [10,39]. Rare species tend to be lost from communities with nutrient enrichment (particularly N) [8].…”
Section: Discussioncontrasting
confidence: 91%
“…Under nutrient enrichment, changes in abundance and richness of native and non-native species were more related to annual climate, whereas under ambient conditions, longterm climate variables were better predictors. Previous studies across these grassland communities have shown that exotic species are more likely to have annual life histories than native species [39]. Furthermore, nutrient enrichment also increases the abundance of non-native species [7,39].…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Dominant species are the small number of species that significantly affect other species (McNaughton & Wolf, 1970; Whittaker, 1965). Due to their high biomass, large size, high productivity, and other traits (Bouchenak‐Khelladi, Slingsby, Verboom, & Bond, 2014; Collins & Duffy, 2016), they can change environmental conditions and resource availability and thus shape community structure (Frieswyk, Johnston, & Zedler, 2007; Okullo, Greve, & Moe, 2013), community diversity (Kunte, 2008; Okullo et al., 2013), community phylogeny (Chalmandrier, Münkemüller, Lavergne, & Thuiller, 2015), trophic structure (Miller, Brodeur, Rau, & Omori, 2010), and ecosystem functions (Behera et al., 2017; Furey, Tecco, Perez‐Harguindeguy, Giorgis, & Grossi, 2014; Grime, 1998; Mokany, Ash, & Roxburgh, 2008; Seabloom et al., 2015). Both dominant species and keystone species are functionally important, but keystone species are much less abundant (Christianou & Ebenman, 2005; Hurlbert, 1997; Mouquet, Gravel, Massol, & Calcagno, 2013; Power et al., 1996).…”
Section: Introductionmentioning
confidence: 99%